Covid-19 Pandemic Goes Endemic: Social Distancing Measures And Use Of Different Digital Platforms In Higher Education - Fouad Boulkroun (The Journal of Studies in Language, Culture and Society, 2024)
In these difficult times of the COVID-19 pandemic and of the implemented social distancing measures, it is not clear how this affects university teachers and whether the digital turn contributes in shaping their affective makeup. The present study aims to investigate the relation between the use of technology and teachers’ affective makeup together with their social and professional connectedness. For this to obtain, three research questions were raised: (1) Is the proportion of teachers who have regular access to the Net the same as the proportion of those whose access is not regular? (2) Are social media platforms users more likely to feel satisfied with what technology offers to stay socially connected than other digital platforms users (namely, blogs, websites, wikis, file sharing sites, etc.)? (3) Is teachers’ satisfaction with what technology offers to stay professionally connected related to type of digital platform used? A questionnaire was administered via email to 161 teachers; only 26 responded. The raw data were submitted to a Chi-square Goodness of Fit test and a Chi-square of Independence test using SPSS. While the results were statistically significant for the former test, they were not so for the latter. Implications and recommendations are thereby discussed.